The Antifungal Effect of Thymus Vulgaris on Isolated Candida Albicans from the Surface of Removable Orthodontic Appliances - Farkhondeh Kavianirad (Herbal Medicines Journal, 2019)
Background and Aim: Orthodontic appliances can impair the balance of oral microflora and increase the load of certain microorganisms in the oral cavity. Chlorhexidine (CHX) is the gold-standard antimicrobial agent for plaque control. However, its long-term use induces adverse effects. The present study seeks to assess the effect of the essential oil of Thymus vulgaris on isolated Candida albicans (C. albicans) from removable orthodontic appliances.